2003
DOI: 10.1046/j.1523-1747.2003.12120.x
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinases on the Body Surface – A Function for p38δ

Abstract: The p38 family of mitogen-activated protein kinases includes p38 alpha (SAPK2a, CSBP), p38 beta (SAPK2b), p38 delta (SAPK4), and p38 gamma (SAPK3/ERK6). p38 alpha and p38 beta are widely expressed p38 isoforms that are involved in regulation of cell proliferation, differentiation, development, and response to stress. Relatively less is known regarding the function of the p38 delta isoform. In this review, we discuss the role of the p38 alpha, p38 beta, and p38 gamma isoforms and then present recent findings th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 101 publications
3
100
0
Order By: Relevance
“…This could be expected, as previous studies indicate that p38␦ is the key p38 isoform involved in regulation of differentiation (6,7,9). A second key issue is whether any such ability of PRMT5 to regulate p38␦ phosphorylation is associated with altered SDMA modification of proteins in the p38␦ signaling complex.…”
Section: Prmt5-dependent Covalent Modification Of Proteins In P38␦ Comentioning
confidence: 74%
See 1 more Smart Citation
“…This could be expected, as previous studies indicate that p38␦ is the key p38 isoform involved in regulation of differentiation (6,7,9). A second key issue is whether any such ability of PRMT5 to regulate p38␦ phosphorylation is associated with altered SDMA modification of proteins in the p38␦ signaling complex.…”
Section: Prmt5-dependent Covalent Modification Of Proteins In P38␦ Comentioning
confidence: 74%
“…Three p38 isoforms, p38␣, p38␤, and p38␦, are expressed in keratinocytes (5,8). Among these, p38␦ has a key role as a positive regulator of keratinocyte differentiation (7). p38␦ mediates the response to differentiating agents including phorbol ester, calcium, okadaic acid, and green tea polyphenol (7,10 -15).…”
mentioning
confidence: 99%
“…Unexpectedly, we found that inhibition of the JNK, p38 MAPK, PKC␦/, and Notch signal pathways affected HO-1 expression in keratinocytes. Considering the fact that the activation of these pathways is tightly connected to keratinocyte differentiation (47)(48)(49)(50), the strict regulation of HO-1 may be critical for keratinocyte differentiation. Because the expression of epidermal proteins is precisely regulated in a temporal and spatial manner, HO-1 expression must be synchronized to that of other proteins during differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This may be important, as p38 is known to enhance differentiation in surface epithelia and may contribute to cell death (52,53). As the four p38 isoforms are known to have differential effects (52,53), additional studies will be required to identify which form is modified by EGCG in our system. Moreover, as noted above, phosphorylation of only selected targets downstream of ERK1/2 is suppressed by EGCG.…”
Section: Egcg Perturbs Cell Cycle Regulators-as Shown Inmentioning
confidence: 99%